THE CONCEPT OF EQUALITY IN EUROPEAN UNION. SOME RE-MARKS ON RECENT LEGAL FRAMEWORK AND JUDICIAL DECI-SIONS - Iwona Wróblewska, Wróblewska (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
The principle of equality is a multi-faceted category. Within the EU, it may be, for instance,  considered in formal or material dimension, as the equality of Member States and the equality of citizens and the institutions of the Member States. This paper focuses on the latter aspect. Keywords: principle of equality, Discrimination, Court of Justice, dignity, freedom and solidarity.